2019
DOI: 10.5897/ajfs2019.1827
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical study of kernel oils from ten varieties of Mangifera indica (Anacardiaceae) cultivated in Cote dIvoire

Abstract: Mango consumers only use pulp and consider the kernel as wastes. This study aims to valorize the kernel of mango (Mangifera indica). In this study, the kernel of ten mango varieties (Ruby, Kent, Retard, Key, Assabony, Smith tête de chat, Smith normal, Palmer, Governeur and Aravia) collected at Yamoussoukro in the center of Cote d'Ivoire were used. The oils of these kernels were extracted by maceration method. Their physicochemical properties were determinate using standard methods. The yields of oils extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
13
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 8 publications
10
13
5
Order By: Relevance
“…Low iodine values of the MKOs reflect their higher resistance to oxidation and longer shelf-life. The lower iodine values of MKOs also indicate that these oils may be used in the manufacture of biodegradable hydraulic fluids, lubricants, soaps, leather, dressings, cosmetics, and in the candle industry. , The present IV values of MKOs are quite comparable to those reported for Thai mangoes but less than those of Nigerian, Malaysian, Saudi, Bangladeshi, Iranian, and Cote d’Ivoire mangoes. ,,,,,, Also, MKOs have lower iodine values (g/100 g) than shea butter (57–66), cottonseed oil (100–105), palm oil (50–55), and cocoa butter (33–42)…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Low iodine values of the MKOs reflect their higher resistance to oxidation and longer shelf-life. The lower iodine values of MKOs also indicate that these oils may be used in the manufacture of biodegradable hydraulic fluids, lubricants, soaps, leather, dressings, cosmetics, and in the candle industry. , The present IV values of MKOs are quite comparable to those reported for Thai mangoes but less than those of Nigerian, Malaysian, Saudi, Bangladeshi, Iranian, and Cote d’Ivoire mangoes. ,,,,,, Also, MKOs have lower iodine values (g/100 g) than shea butter (57–66), cottonseed oil (100–105), palm oil (50–55), and cocoa butter (33–42)…”
Section: Resultssupporting
confidence: 52%
“…The color of MKOs, as determined by a tint meter, in terms of yellow and red units, is quite acceptable as far as edible and industrial applications are concerned. 13,15,18,23,27,32 but higher than those reported for Nigerian, Kenyan, and Thai mangoes. 7,25,33 The refractive index (RI) increases with the unsaturation or with the presence of secondary functional groups on the fatty chains.…”
Section: Yield Of Mango Kernel Oils (Mkos)mentioning
confidence: 80%
See 2 more Smart Citations
“…These are eco‐friendly techniques and are associated with decreased processing duration, lower consumption of solvent, and enhanced quality of the final product (Bimakr, Ghoreishi, et al, 2019). A number of previous studies have reported the extraction of mango kernel butter using conventional techniques (Abdel‐Razik et al, 2012; Kassi et al, 2019; Nzikou et al, 2010) while limited studies have been undertaken for comparative evaluation of various green techniques including ultrasound‐assisted extraction (UAE), microwave‐assisted extraction (MAE), and SCFE for the extraction of mango kernel butter. Among all the novel techniques, ultrasonication could be a simple and cost‐effective substitute for conventional techniques (Bimakr, Ganjloo, & Noroozi, 2019).…”
Section: Introductionmentioning
confidence: 99%